HUGE SUB-MANDIBULAR GLAND TUMOUR - Waqar, Waqar SH; Malik, Zafar Iqbal; Zahid, Zahid MA (Journal of Ayub Medical College Abbottabad, 2011)
Salivary gland neoplasms are a diverse group of tumours and appropriate treatment depends on adequate understanding of the pathophysiologic behaviour of each tumour type. Most (95%) salivary glands occur in adults. Benign tumours are slow growing tumours and attain a considerable size before presenting to surgeon. We report a case of huge tumour of left submandibular gland that presented in our surgical outpatient department, and had developed over last twenty years. It was diagnosed as a benign mixed tumour of salivary gland and was successfully excised. Histopathology confirmed it to be a benign pleomorphic adenoma. Keywords: Salivary gland neoplasm, Sub-mandibular gland, Pleomorphic adenoma